2021
DOI: 10.1101/2021.01.04.21249195
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The incidence, characteristics and outcomes of pregnant women hospitalized with symptomatic and asymptomatic SARS-CoV-2 infection in the UK from March to September 2020: a national cohort study using the UK Obstetric Surveillance System (UKOSS)

Abstract: BackgroundEvidence on risk factors, incidence and impact of SARS-CoV-2 infection in pregnant mothers and their babies has rapidly expanded but there is a lack of population level data to inform accurate incidence rates and unbiased descriptions of characteristics and outcomes. The primary aim of this study was to describe the incidence, characteristics and outcomes of hospitalized pregnant women with symptomatic and asymptomatic SARS-CoV-2 in the UK compared to pregnant women without SARS-CoV-2 in order to inf… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 18 publications
1
13
0
2
Order By: Relevance
“…Minority ethnicity has been identified as a risk factor for SARS-CoV-2 infection in both pregnant and non-pregnant women. [5][6][7][8]11 The increased risk level found in this study is similar to that reported in a large systematic review. 5 The aetiology of the ethnic disparity is not clear, but it is probably multifaceted and related to cultural and socioeconomic factors rather than to SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Minority ethnicity has been identified as a risk factor for SARS-CoV-2 infection in both pregnant and non-pregnant women. [5][6][7][8]11 The increased risk level found in this study is similar to that reported in a large systematic review. 5 The aetiology of the ethnic disparity is not clear, but it is probably multifaceted and related to cultural and socioeconomic factors rather than to SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, the outcomes are in most studies compared to outcomes of historic cohorts of non-infected women, with the risk that the consequences of the pandemic will be attributed solely to SARS-CoV-2. 6,7,11 Lastly, testing strategies influence the estimated prevalence of SARS-CoV-2 infection, and potentially also the estimated severity of outcomes in that also the mild and asymptomatic cases detected. 5 The testing strategy in Denmark rapidly evolved during the pandemic from testing the most ill in March 2020 to testing cases with mild symptoms from April and testing close contacts from May.…”
Section: Main Body Of Text Introductionmentioning
confidence: 99%
“…These strategies varied over time and between countries during the inclusion period (Figure S1) and could have biased the study results otherwise. Large population-based cohort studies from the United Kingdom (UK) and Italy found an incidence of hospitalization with COVID-19 of 2 -4.9/1000 maternities (13)(14)(15), which is much higher than the risk of 0.4/1000 deliveries found in DK, FI, IS and NO. However, these studies included admissions for any reason, such as obstetric care and labour.…”
Section: Accepted Articlementioning
confidence: 93%
“…With the on-going pandemic, population-based studies with larger case numbers and lower risk of bias are crucial for guiding disease surveillance and health management (12). A few population-based studies assessing the risk and consequences of COVID-19 infection in pregnancy have been published (13)(14)(15). However, the inclusion criteria comprised all causes of hospital admission which results in heterogenous study populations.…”
Section: Introductionmentioning
confidence: 99%
“…Ризики мертвонародження чи неонатальної летальності не були значно збільшені, тому ця статистика не бралася до уваги. [6].…”
unclassified